Consistency Analisis Between Regional Development Work Plan Document, The Provisional Budget Ceiling, and Priority, As Well As Budget Revwnue and Spending Areas in Magelang City Government - Maya Kumalasari; Abdul Halim (The Indonesian Journal of Accounting Research, 2016)
Abstract: The lack of information related to the resources owned by the government caused the Government has to do planning and budgeting properly. Development planning in the form of a document will be useless if it is not linked to budgeting. The consistency between planning and budgeting documents is indispensable so that the development goals can be achieved optimally. However, in reality, it is still often a planning document has not fully become a guide for the next process, namely budgeting. Therefore, this research analyzes the consistency level between planning and budgeting documents as follows RKPD, KUA, PPAS, and APBD. Furthermore, this research aims to explore more in-depth the inconsistencies between planning and budgeting. This research uses a qualitative method, and the objective of the study is Magelang City Government. The informants of this research are employees that directly involved in planning and budgeting. Data analysis results show that there are inconsistencies in 2014 and 2015. The process that needs to be concerned is the APBD process preparation in which according to the data analysis becomes the most susceptible process of inconsistency. There are several factors leading to inconsistencies include low understanding of planning and budgeting from the executive, legislative, society and DPRD intervention, lack of joint commitment from stakeholders and policymakers, the use of different applications, there are no clear sanctions in case of inconsistency, lack of attention to the consistency of performance indicators as well as policies from the central government that are often late to deliver. Abstract: Kurangnya informasi yang terkait dengan sumber daya yang dimiliki oleh pemerintah menyebabkan Pemerintah harus melakukan perencanaan dan penganggaran dengan benar. Perencanaan pembangunan dalam bentuk dokumen tidak akan berguna jika tidak dikaitkan dengan penganggaran. Konsistensi antara dokumen perencanaan dan penganggaran sangat diperlukan agar tujuan pembangunan dapat tercapai secara optimal. Namun, kenyataannya, masih sering dokumen perencanaan belum sepenuhnya menjadi panduan untuk proses selanjutnya, yaitu penganggaran. Oleh karena itu, penelitian ini menganalisis tingkat konsistensi antara dokumen perencanaan dan penganggaran sebagai berikut RKPD, KUA, PPAS, dan APBD. Selanjutnya, penelitian ini bertujuan untuk menggali lebih mendalam ketidakkonsistenan antara perencanaan dan penganggaran. Penelitian ini menggunakan metode kualitatif, dan tujuan penelitian ini adalah Pemerintah Kota Magelang. Informan penelitian ini adalah karyawan yang terlibat langsung dalam perencanaan dan penganggaran. Hasil analisis data menunjukkan bahwa terdapat inkonsistensi pada tahun 2014 dan 2015. Proses yang perlu diperhatikan adalah persiapan proses APBD yang menurut analisis data menjadi proses inkonsistensi yang paling rentan. Ada beberapa faktor yang menyebabkan inkonsistensi termasuk rendahnya pemahaman tentang perencanaan dan penganggaran dari intervensi eksekutif, legislatif, masyarakat dan DPRD, kurangnya komitmen bersama dari pemangku kepentingan dan pembuat kebijakan, penggunaan aplikasi yang berbeda, tidak ada sanksi yang jelas dalam kasus inkonsistensi, kurangnya perhatian pada konsistensi indikator kinerja serta kebijakan dari pemerintah pusat yang sering terlambat disampaikan.